Effects of intradialytic exercise on physical and psychological outcomes in patients undergoing hemodialysis: A systematic review - Indra Frana Jaya KK; Novi Yanti S; Ayu Prawesti Priambodo (Lentera Perawat, 2026)
Background: Patients undergoing maintenance hemodialysis frequently experience physical and psychological problems, including fatigue, reduced functional capacity, muscle weakness, anxiety, stress, depression, and a decline in quality of life. These conditions are influenced by chronic kidney disease, long-term hemodialysis, limitations in physical activity, and dependence on dialysis therapy. Intradialytic exercise, defined as physical exercise performed during a hemodialysis session, is a nonpharmacological intervention with the potential to improve patients' physical and psychological conditions. Objective: To evaluate the effectiveness of intradialytic exercise on physical and psychological outcomes in patients undergoing hemodialysis. Methods: This systematic review was conducted in accordance with the PRISMA guidelines and was registered in PROSPERO under registration number CRD420261386106. Literature searches were conducted in PubMed, ScienceDirect, Scopus, Web of Science, and CINAHL. Articles published from 2020 to 2026 were searched, with the final search conducted in May 2026. The included studies were quantitative studies, primarily randomized controlled trials, quasi-experimental studies, or other intervention studies that evaluated exercise performed during hemodialysis and reported physical and/or psychological outcomes. Study selection, data extraction, and quality assessment were performed independently by the reviewers. A total of 18 studies met the inclusion criteria and were analyzed in this systematic review. Results: The synthesis showed that intradialytic exercise had positive effects on physical outcomes, including improvements in functional capacity, muscle strength, activity tolerance, and physical performance, as well as reductions in fatigue. Several studies also reported improvements in psychological outcomes, including reductions in anxiety, stress, and depression and improvements in quality of life. Conclusion: Intradialytic exercise may be an effective nonpharmacological intervention for improving physical and psychological outcomes in patients undergoing hemodialysis, while taking into account each patient's clinical condition, safety, and individual capabilities.